Formation of nanoscale carbon structures in the surface layer of metals under the impact of high intensity ion beam; Applied Surface Science; Vol. 310 - Remnev G. E. Gennady Efimovich; Uglov V. V. Vladimir Vasilievich; Shimanskii (Shymanski) V. I. Vitali Igorevich; Pavlov S. K. Sergey Konstantinovich; Kuleshov A. K. (2014, 2014)
Title screen